Process analysis of the patient pathway for automated data collection: an exemplar using pituitary surgery - Hanrahan, John G.; Carter, Alexander W.; Khan, Danyal Z.; Funnell, Jonathan P.; Williams, Simon C.; Dorward, Neil L.; Baldeweg, Stephanie E.; Marcus, Hani J. (Frontiers in Endocrinology, 2024)
This is a provisional file, not the final typeset article treatment decisions (N = 88, 6.12%) representing critical data points. Operation notes and neurosurgical ward round entries were present for every patient. 43/44 (97.7%) had a pre-operative pituitary MDT entry, pre-operative clinic letter, a post-operative clinic letter, an admission clerking entry, a discharge summary, and a post-operative histopathology pituitary multidisciplinary (MDT) team entries.This is the first study to produce a validated patient pathway of patients undergoing pituitary surgery, serving as a comparison to optimise this patient pathway. We have identified salient targets for structured data entry interventions, including mandatory datapoints seen in every admission and have also identified areas to improve documentation adherence, both of which support movement towards automation.